TGF-β and new bone formation - Issa, João Paulo Mardegan; Tiossi, Rodrigo; Pitol, Dimitrius Leonardo [UNESP]; Mello, Amaro Sérgio Da Silva (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2006)
The aim of this work is to present, by a literature review, the principal characteristics of TGF-beta, in the regulation and new bone formation. © 2007 Sociedad Chilena de Anatomía.
Keywords: Bone; TGF-beta